Upaya Meningkatkan Servis Bawah Bola Voli dengan Media Bola Spoon - Moch Hisa Ardiansah; Iva Alivatul Kartikasari; Febi Bahru Adilah; Elang Romadho; Hodri Taufik (Jurnal Simki Postgraduate, 2024)
The challenge often encountered by teachers during learning activities is related to underhand serving, where students struggle to achieve the expected learning objectives. This research aims to improve students' ability to perform underhand serves using lightweight plastic balls in Class V at SDN Mojoroto 2, Kediri City. The research method employed is Classroom Action Research (CAR). In this study, the subjects involved were teachers collaborating with 28 fifth-grade students at SDN Mojoroto 2. The results of the study showed a positive impact on students through the implementation of two cycles, which included stages of planning, implementation, observation, and reflection. In the first cycle, 23 students (82%) successfully achieved the learning objectives, while 5 students (18%) had not yet succeeded. The research continued to the second cycle, providing students with opportunities to improve their underhand serving skills by gradually practicing with plastic balls. By the end of the second cycle, all 28 students (100%) successfully passed, with no students remaining unsuccessful.